Protocol for a scoping review of the use of information and communication technology platforms for the delivery and utilisation of transgender healthcare - Muhammad Naveed Noor; Isaac Yeboah Addo; Jialiang Cui; Sujith Kumar Prankumar; Horas TH Wong; Christopher Tumwine (BMJ Open)
Introduction In recent years, there has been strong interest in making digital health and social tools more accessible, particularly among vulnerable and stigmatised groups such as transgender people. While transgender people experience unique physical, mental and sexual health needs, not much is currently known about the extent to which they use information and communication technologies such as short messaging service and videoconferencing to access health services. In this paper, we discuss our protocol for a scoping review of the literature about the delivery and utilisation of digitally mediated health services for transgender populations.Methods and analysis This scoping review of the provision and experience of telemedicine among transgender people will follow the methodological framework developed by Arksey and O’Malley. The search will be conducted using three online databases, namely PubMed, CINAHL and Scopus, with additional literature explored using Google Scholar to identify grey literature. Relevant English-language studies will be shortlisted after completing a title and abstract review based on defined inclusion criteria. Following that, a final list of included studies will be compiled after a full-text review of the shortlisted articles has been completed. To enable the screening process, a team of researchers will be assigned refereed publications explicitly referring to the provision and experience of transgender healthcare through telemedicine. Screening performed independently will then collaboratively be reviewed to maintain consistency.Ethics and dissemination The research is exempt from ethics approval since our analysis is based on extant research into the use of digital technologies in providing healthcare to transgender people. The results of this study will be disseminated through peer-reviewed academic publications and presentations. Our analysis will guide the design of further research and practice relating to the use of digital communication technologies to deliver healthcare services to transgender people.